THE EFFECT OF DEVELOPING MIND MAPS ON STUDENTS’ ABILITY IN WRITING HORTATORY EXPOSITION TEXTS - Diah Paramita Sari (Politeknik Negeri Bengkalis, 2016)
Abstract: Mind mapping is a way to store and to take the ideas out of the brain then to present ideas visually to show the hierarchical relationship of ideas. The purpose of this research was to see the effect of making mind mapping as a writing activity towards students’ ability in writing hortatory exposition texts. This research was an experimental research. It was conducted at SMA 5 Padang. Population of this research was eleventh year students of SMA 5 Padang. The sample was taken by cluster sampling. 11 IPA1 was experimental class and 11 IPA2 was control class. The data indicates that the result of pre test and posttest from the two groups: experimental and control group is different. The different could be seen from the hypothesis testing. T-obtained was bigger than t-table. It meant that the difference of the meant scores of the experimental and control group is significant. In short, making mind mapping as a technique in writing hortatory text gives positive effect on students’ ability in writing hortatory exposition text. For further researcher, they can apply this technique to other skills and others kinds of text. Keywords: Mind Mapping, Hortatory Exposition Text, Writing